2022
DOI: 10.1021/acsnano.2c08684
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted High-Performance Lithium Anode Enabled by Oriented Crystal Planes

Abstract: Lithium (Li) metal anodes are candidates for the next-generation high-performance lithium-ion batteries (LIBs). However, uncontrolable Li dendrite growth leads to safety issues and a low Coulombic efficiency (CE), which hinders the commercialization of Li metal batteries. Stable Li anodes based on the tailored plane deposition and photoassisted synergistic current collectors are currently the subject of research; however, there are few related studies. To suppress the growth of Li dendrites and achieve dense L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Photo-assisted Li-metal battery, reproduced by permission. 14 Copyright 2022, American Chemical Society. Photo-assisted Zn-Te battery, reproduced by permission.…”
Section: Working Principle Of Photoassisted Rechargeable Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Photo-assisted Li-metal battery, reproduced by permission. 14 Copyright 2022, American Chemical Society. Photo-assisted Zn-Te battery, reproduced by permission.…”
Section: Working Principle Of Photoassisted Rechargeable Batteriesmentioning
confidence: 99%
“…[7][8][9][10] For integrated energy storage systems, photo-assisted rechargeable batteries are among the most efficient. [11][12][13][14][15] The asdesigned photo-assisted rechargeable batteries provide a potential way to utilize sunlight on a large scale and achieve effective, more economical, durable and environmentally friendly integration of solar energy into chemical energy in the batteries. People have been working on photo-assisted charging battery devices lately because they can effectively convert and store solar energy directly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on increasing the energy density of rechargeable lithium-ion batteries (LIBs), lithium metal with a high theoretical specific capacity (3860 mAh g −1 ) and low redox potential (−3.040 V vs. standard hydrogen electrode) have been extensively investigated [1][2][3][4]. However, uncontrollable lithium dendrite growth and dead lithium (inactive lithium) generation during repeated cycles lead to instability at the lithium metal anode interface, which results in a waste of lithium resources, a low Coulombic efficiency (CE), and even incurs safety hazards, which seriously restrict their practical applications [5][6][7][8]. Many efforts such as the construction of three-dimensional (3D) skeletal structures, loads with lithiophilic active sites, prepositioned artificial solid electrolyte interphases (SEI), and separator modifications have been devoted to tackle the above issues [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage of PBAs is their low crystal density. However, recent work found that composite materials combining PBA with other materials (such as oxides, sulfides, selenides, phosphates, borides, and carbides) can effectively neutralize the defects of the two materials [ 8 ]. When composite materials are used in energy storage, their cycle and electrochemical properties can improve significantly.…”
Section: Introductionmentioning
confidence: 99%